Socioeconomic Disparities in the Prevalence, Diagnosis, and Control of Hypertension in the Context of a Universal Health Insurance System - Lee, Hoo-Yeon (J Korean Med Sci, 2017)
A lower use of preventive intervention in low socioeconomic populations has been described in countries with universal coverage health care systems, but little is known about the possible socioeconomic inequalities in secondary prevention in a universal health insurance system. Data from the 2010-2013 Korea National Health and Nutrition Examination Survey, a nationwide survey, were analyzed. A total of 20,044 subjects older than 30 years of age were included after excluding subjects with missing data. Prevalence ratios were calculated using Poisson regression models with robust variance to explore factors associated with the prevalence, unawareness, and inappropriate control of hypertension. Hypertension prevalence decreased with increasing education and income level. We observed an inverse association between education level and undiagnosed hypertension among women, but not men. Socioeconomic level was not associated with inadequate control of hypertension among men or women. Future interventions should include primary prevention efforts targeted at lower socioeconomic populations to reduce disparities. There is substantial room for improvement in secondary prevention efforts. Monitoring strategies may highlight gaps in the preventive and care services offered to the most vulnerable individuals and encourage governments and practitioners to address these gaps.